2011
DOI: 10.1164/rccm.201002-0304oc
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Expression in Induced Sputum of Smokers and Patients with Chronic Obstructive Pulmonary Disease

Abstract: let-7c is significantly reduced in the sputum of currently smoking patients with COPD and is associated with increased expression of TNFR-II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
186
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 217 publications
(195 citation statements)
references
References 46 publications
6
186
2
1
Order By: Relevance
“…Cancer 13, 233-245 (2013)) 1 , McGarry Houghton reviewed the association between the presence of chronic obstructive pulmonary disease (COPD) and the development of lung cancer and suggested that genetic and epi genetic changes, inflammation and associated cytokines, smoking, alterations to cell cycle regulation and the presence of specific proteinases produced by immune cells and other stromal cells could be involved in this association. However, even though the review provided an entire and holistic view of this clinically relevant subject, we would like to add microRNAs (miRNAs) and especially the miRNA let-7c as an important pathogenic link between COPD and lung cancer.Pottelberge et al 2 recently reported that let-7c was significantly reduced among 627 miRNAs in the sputum of patients with COPD who currently smoke compared with never smokers. The decreased expression of let-7c was associated with an increased expression of soluble tumour necrosis factor receptor 2 (TNFR2): TNFR2 mRNA is a predicted target of let-7c and is implicated in COPD pathogenesis.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Cancer 13, 233-245 (2013)) 1 , McGarry Houghton reviewed the association between the presence of chronic obstructive pulmonary disease (COPD) and the development of lung cancer and suggested that genetic and epi genetic changes, inflammation and associated cytokines, smoking, alterations to cell cycle regulation and the presence of specific proteinases produced by immune cells and other stromal cells could be involved in this association. However, even though the review provided an entire and holistic view of this clinically relevant subject, we would like to add microRNAs (miRNAs) and especially the miRNA let-7c as an important pathogenic link between COPD and lung cancer.Pottelberge et al 2 recently reported that let-7c was significantly reduced among 627 miRNAs in the sputum of patients with COPD who currently smoke compared with never smokers. The decreased expression of let-7c was associated with an increased expression of soluble tumour necrosis factor receptor 2 (TNFR2): TNFR2 mRNA is a predicted target of let-7c and is implicated in COPD pathogenesis.…”
mentioning
confidence: 99%
“…Pottelberge et al 2 recently reported that let-7c was significantly reduced among 627 miRNAs in the sputum of patients with COPD who currently smoke compared with never smokers. The decreased expression of let-7c was associated with an increased expression of soluble tumour necrosis factor receptor 2 (TNFR2): TNFR2 mRNA is a predicted target of let-7c and is implicated in COPD pathogenesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The role of miRNAs in the altered immune responses and homeostatic mechanisms of COPD is beginning to emerge. 34 miRNAs were found to be differentially expressed in induced sputum from never-smokers compared with current smokers without COPD, while eight miRNAs were significantly reduced in current smokers with COPD compared to never-smokers (miR-34c, miR-218, miR-34b, let-7c, miR-342-3p, miR-125a-5p, miR-30e-3p and miR-125b) [113]. Levels of let7c significantly inversely correlated with protein levels of TNF receptor type II (TNFR-II), which is implicated in the pathogenesis of COPD.…”
Section: B-cellsmentioning
confidence: 97%
“…At present, seventy miRNAs have been found to be differentially expressed in lung whole tissue between smoking patients affected by COPD and smokers not affected by COPD [4]. However, many of the study results have only been inconsistently replicated using different miRNA expression datasets [5]. It is for this reason, that many of the findings cannot be well synthesized and interpreted.…”
Section: Introductionmentioning
confidence: 95%